2015
DOI: 10.2355/isijinternational.55.183
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Phosphorus in Steelmaking Slags and Aquatic Particulate Materials Using a Sequential Extraction Technique

Abstract: We measured the concentrations and chemical forms of phosphorus (P), an essential nutrient in marine ecosystems, in steelmaking slag (Slag) to determine whether use of Slags as a basal medium for artificial tidal flats and seagrass beds was an environmentally acceptable option for the reuse and recycling of Slags. We tested six Slag samples, including dephosphorization slags and converter slags. The total P concentrations were one order of magnitude higher in the Slags than in the aquatic particulate materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Steelmaking slags contain a considerable amount of calcium oxide (Kourounis et al 2007;Tsukasaki et al 2015). As a result, the possibility of an increase in the pH of the pore water and the overlying seawater due to dissolution of calcium from slags is a matter of concern (Asaoka et al 2013).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Steelmaking slags contain a considerable amount of calcium oxide (Kourounis et al 2007;Tsukasaki et al 2015). As a result, the possibility of an increase in the pH of the pore water and the overlying seawater due to dissolution of calcium from slags is a matter of concern (Asaoka et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…However, it is important to note that not all the phosphorus in slag is biologically available; a considerable part is tightly bound to or entrapped in slag particles. By using a sequential extraction technique for chemical fractionation of various forms of phosphorus, Tsukasaki et al (2015) showed that the amount of phosphorus mobilized under natural marine conditions (mobile P) varied widely, depending on the type of slag. In the slag and DM used in this core experiment, 30.4 and 45.2 % of TP, respectively, was mobile P. We therefore recalculated the integrated phosphate loss by diffusion using these values and concluded that a large amount of mobile P (>99 %) remained in the slag-based sediments after 379 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one kind of mass industrial solid waste, open dumping of steel slag not only occupies land but causes potential pollution by dust as well as the alkalinity to air, soil and groundwater (Asuman Korkusuz et al, 2007). Attentions has been attracted to the use of steel slags as potential adsorbents in regulating the phosphorus cycle through uptake from and slowly release to the water as well as alternatives to the basal medium for construction of artificial wetland, tidal flats and seagrass beds recently (Claveau-Mallet et al, 2014;Hayashi et al, 2011;Hussain et al, 2015;Tsukasaki et al, 2015;Yamamoto and Liu, 2013). Among variety slags generated from different steelmaking processes, slag from the basic oxygen furnace (BOFS) presents the highest phosphorus adsorption capacity (Barca et al, 2012;Oguz, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FeO and P2O5 in the slag could be utilized, that could be one of the main burden to produce iron and phosphorus compounds [2]. Besides, the slag was able to be recycled to make constructive materials as indicated in the research of Tsukasaki and co-workers [3]. The application of the slag have been explored in term of the agglomeration of iron ore or pretreatment processes as well [4][5][6].…”
Section: Introductionmentioning
confidence: 99%